Targeting water utilities for the threshold problem without waste discharge - Parand, Reza; Yao, Hong; Tade, Moses; Pareek, Vishnu (Institute of Chemical Engineers (IchemE), Elsevier B.V., 2013)
Increasing water scarcity and stringent environmental regulation have necessitated effective water conservation policies. Pinch analysis has been proved as one of the powerful tools to locate targets of waste water minimization. Two earlier water pinch targeting methods known as Water Cascade Analysis and Material Recovery Pinch Diagram have focused on the “threshold problems”. However, these methodologies have not systematically analyzed the introduction of external utility. In this work, three scenarios are proposed for this reason. The “Infeasible Threshold Problem” is addressed prior to employing external utility through the proposed scenarios. By systematically analyzing this specific problem, it is revealed that existing Water Cascade Analysis method cannot locate correct infeasible targets. Some adjustments are proposed to deal with this drawback. Moreover, to illustrate the applicability of proposed scenarios, Water Cascade Analysis and Material Recovery Pinch Diagram approaches are utilized for addressing a literature problem as a case study. It is shown that harvesting the impure fresh water source with a higher quality, in the “threshold problem with zero discharge”, leads to more pure fresh water saving.